2004
DOI: 10.1021/jo0492160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Changing Electrophilic Center from CO to CS on Rates and Mechanism:  Pyridinolyses of O-2,4-Dinitrophenyl Thionobenzoate and Its Oxygen Analogue

Abstract: Second-order rate constants have been measured spectrophotometrically for the reactions of O-2,4-dinitrophenyl thionobenzoate (1) and 2,4-dinitrophenyl benzoate (2) with a series of substituted pyridines in 80 mol % H(2)O/20 mol % DMSO at 25.0 +/- 0.1 degrees C. The Brønsted-type plots obtained are nonlinear with beta(1) = 0.26, beta(2) = 1.07, and pK(a) degrees = 7.5 for the reactions of 1 and beta(1) = 0.40, beta(2) = 0.90, and pK(a) degrees = 9.5 for the reactions of 2, suggesting that the pyridinolyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…1-10 Aminolysis of carboxylic esters has generally been proposed to proceed through a stepwise mechanism with a zwitterionic tetrahedral intermediate T ± on the basis of curved Brønsted-type plots reported for reactions of esters possessing a good leaving group (e.g., 2,4-dinitrophenoxide). [1][2][3][4][5][6][7][8][9][10] The rate-determining step (RDS) has been suggested to be dependent on the basicity of the incoming amine and the leaving group, i.e., it changes at pK a o , defined as the pK a at the center of the Brønsted curvature, 9,10 from breakdown of T ± to its formation as the incoming amine becomes more basic than the leaving group by 4 to 5 pK a units. [1][2][3][4][5][6][7][8][9][10] Aminolysis of thiono esters has been reported to proceed through one or two intermediates (i.e., T ± and its deprotonated form T -) depending on the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1-10 Aminolysis of carboxylic esters has generally been proposed to proceed through a stepwise mechanism with a zwitterionic tetrahedral intermediate T ± on the basis of curved Brønsted-type plots reported for reactions of esters possessing a good leaving group (e.g., 2,4-dinitrophenoxide). [1][2][3][4][5][6][7][8][9][10] The rate-determining step (RDS) has been suggested to be dependent on the basicity of the incoming amine and the leaving group, i.e., it changes at pK a o , defined as the pK a at the center of the Brønsted curvature, 9,10 from breakdown of T ± to its formation as the incoming amine becomes more basic than the leaving group by 4 to 5 pK a units. [1][2][3][4][5][6][7][8][9][10] Aminolysis of thiono esters has been reported to proceed through one or two intermediates (i.e., T ± and its deprotonated form T -) depending on the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The rate-determining step (RDS) has been suggested to be dependent on the basicity of the incoming amine and the leaving group, i.e., it changes at pK a o , defined as the pK a at the center of the Brønsted curvature, 9,10 from breakdown of T ± to its formation as the incoming amine becomes more basic than the leaving group by 4 to 5 pK a units. [1][2][3][4][5][6][7][8][9][10] Aminolysis of thiono esters has been reported to proceed through one or two intermediates (i.e., T ± and its deprotonated form T -) depending on the reaction conditions. 5 Castro et al have reported that reactions of 4-nitrophenyl phenyl thionocarbonate with strongly basic amines proceed through T ± while those with weakly basic amines proceed through T ± and T -.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations